Mutual Relationship Between Sleep Disorders, Quality of Life and Psychosocial Aspects in Patients With Psoriasis - Nowowiejska, Julia; Baran, Anna; Flisiak, Iwona (Frontiers in Psychiatry, 2021)
Psoriasis is a chronic, autoimmune skin disease affecting about 2-4% of worldwide population. It is now perceived as a systemic disease because of the complex pathogenesis and multiple comorbidities. It leads to decreased life quality and productivity of the patients. Nowadays sleep disorders are investigated as well in relation to psoriasis as another possible comorbidity. The review focuses on possible negative effects of sleep deprivation, decreased life quality and psychosocial status in psoriatic patients and highlights their mutual, complex relationship of a divergent consequences. The relationship between sleep disorders and psychosocial status in psoriatics is bidirectional and resembles vicious circle, one abnormality triggering the other. Sleep disorders additionally increase the risk of metabolic and psychiatric diseases in psoriatic patients who already have this possibility increased. There should be measures taken to screen psoriatics for sleep disorders in order to early diagnose and treat.